2021
DOI: 10.1101/2021.04.22.21255586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An emerging role of microplastics in the etiology of lung ground glass nodules

Abstract: Pulmonary ground glass nodules (GGNs) have been increasingly identified in past decades and is becoming an important clinical dilemma in oncology. Meanwhile, humans persistently inhale microplastics which are dominant in the air. However, the retention of “non-self” microplastics in human lung and its correlation with pulmonary GGNs remains elusive. In this study, we firstly demonstrated the presence of microfibers and microplastics in human lung, with higher detection rates in GGNs in comparison to those in n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In addition, a previous study reported that lung cancer survivors were more vulnerable to subsequent pulmonary malignancies (32). In 2021, Chen et al first demonstrated that microplastic exposure was associated with the etiology of multiple pulmonary GGOs (ground-glass nodules) (33), linking MPLC pathogenesis to environmental factors. Genetic variants, such as EGFR germline mutations, were also reported to be the driving force of MPLC (15,34).…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
“…In addition, a previous study reported that lung cancer survivors were more vulnerable to subsequent pulmonary malignancies (32). In 2021, Chen et al first demonstrated that microplastic exposure was associated with the etiology of multiple pulmonary GGOs (ground-glass nodules) (33), linking MPLC pathogenesis to environmental factors. Genetic variants, such as EGFR germline mutations, were also reported to be the driving force of MPLC (15,34).…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
“…These findings reinforce the damaging effects of MPs in cigarette butts. 64 Although the cigarette filter has been understood as a barrier that aims to eliminate toxins, thus reducing damage, it is currently known that it does not offer health benefits to smokers. Cigarette filters are composed of more than 15,000 fiber strands which can be put into a microfiber size range (microfiber/MP) or eventually get fragmented into smaller sizes.…”
Section: Inhalationmentioning
confidence: 99%